Polyoxometalates as bifunctional templates: engineering metal oxides with mesopores and reactive surfaces for catalysis. Issue 48 (25th November 2019) - Leng, Yan; Liu, Jixing; Zhang, Zihao; Chen, Hao; Zhang, Pengfei; Dai, Sheng
Abstract : For the first time, Keggin type POMs were found to be excellent bifunctional templates for generating not only mesopores but also reactive surfaces in metal oxides. Abstract : Mesoporous metal oxides with optimized porosity and active surfaces usually exhibit unexpected performance in many applications. However, sacrificial templates and complicated processes are generally required to generate mesopores. Herein, we discover the bifunctional templating talent of polyoxometalates (POMs) for generating not only mesopores but also reactive surfaces in metal oxides, and a facile, recyclable, and general method is reported. By mechanochemical ion-sharing between metal salts and POMs, metal precursors undergo pyrolysis around large POM clusters, which can incorporate abundant mesopores into metal oxides ( e.g., Co3 O4, Fe3 O4, NiO, La2 O3, MnO2, CeO2, ZrO2, and CuO) with ultrahigh specific surface areas (up to 210 m 2 g −1 ) after simply being recycled by water washing. Unexpectedly, the oxidative feature of POMs naturally contributes to the formation of high valence metal cations on the material surface. As an example, the Co3 O4 sample with both mesopores and enriched surface Co 3+ species was more active than Co3 O4 derived from a silica template ( T 100 = 200 °C) and commercial Co3 O4 ( T 100 = 250 °C), in CO oxidation. The current strategy may provide a promising route for the commercialization of mesoporous metal oxides with preferred surface features.